Makna simbolik gerak tari halibambang - Susi Wendhaningsih; Dwiyana Habsary (Universitas Lampung, 2021)
This thesis explores the significance of the symbols in the Halibambang dance. These concepts can be traced back to the dance gestures, costumes and assets of the Halibambang dance.The study review focuses on the sense of motion and is related to the principles held by the people of Lampung. The approach used in this research is ethnocoreology. The Halibambang dance is one of the many dances that originate in the Saibatin tradition. It's a dance that's performed in groups. This dance is performed by the woman, and this dance represents the nature of the butterflies. The concept that can be studied apart from the name and the movement of the dance. Results have shown that the sense of the Halibambang. The results showed that the sense of the Halibambang dance movement describes the behavior of people of Lampung, and the movements used also reflect the livelihoods of the Saibatin people. Keywords: Meaning of Symbolic, Dance Movement, Halibambang Dance